Employers' and lecturers' perceptions of graduates' work readiness based on their generic skills / Zubaidah Abdul Ghani - Abdul Ghani, Zubaidah (2012)
The role of Higher Learning Institutions and how they should meet the needs of the employers in the 21st century has become a greater concern. The issue regarding graduates’ inability to meet the employers’ demands was also always related to misconception on what is required by employers. Driven by this concern, this study is to determine the perception of employers and lecturers towards graduates’ work readiness as indicated by their generic skills. More specifically, this study is to determine the priorities of generic skills in terms of rank as perceived by the employers and lecturers. This study employed a descriptive method research design which entailed a research instrument in the form o f a questionnaire. The study involved a total of 33 respondents from private sector employers and 58 lecturers from public universities. The findings show that the employers’ perception indicates "integrity and professional ethics” but the lecturers’ perception indicates "communication skills”. Considering that the highest generic skills that are currently being taught in universities is “teamwork” and considering that the skill that is most sought after by employers are “integrity and professional ethics”, there seems to be a mismatch between what the employers expect what the university is emphasizing. In terms of rank, both employers and lecturers prioritize “communication skills” as the most important generic skills as required by fresh graduates. This study also indicates that both multinational and local employers and both social science and science lecturers prioritize “communication skills” as the most important generic skills as required by fresh graduates. From these findings, immediate action and necessary steps should be taken into consideration in order to emphasize and integrate “communication skills” in HLIs. The mismatch between the employers’ demand and the university’s emphasis should also be addressed to improve graduates’ employability. In future research, it is recommended that the variables in prioritizing the importance of generic skills should include the difference between public universities and private universities students or lecturers.